IMPROVING FINE MOTOR SKILLS OF 4–5 YEAR OLD CHILDREN THROUGH BOTTLE CAP MEDIA - Sukarni; Pipit Nuri Mulyaningtias; Noor Ishma (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This research aims to improve fine motor skills of children aged 4–5 years through the use of bottle cap media at PAUD Az-Zahra Rengas, South Tangerang City. The background of the study is based on the importance of stimulating fine motor development in early childhood, who are in the golden age period where finger coordination, wrist movement, and manipulative skills are crucial to support learning readiness at the next level. The research method employed was Classroom Action Research (CAR) using the Kemmis and Taggart model, carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were 17 children, consisting of 8 boys and 9 girls. Data were collected through observation, documentation, and field notes, then analyzed qualitatively and quantitatively to examine the development of children’s fine motor skills. The findings revealed a significant improvement after the application of bottle cap media, where in the pre-cycle the average mastery level was only 45.9%, increasing to 70.8% in the first cycle, and reaching 99.9% in the second cycle, which exceeded the success indicator of 80%. This improvement was reflected in the children’s ability to classify, arrange, and manipulate bottle caps effectively, indicating optimal development of their fine motor skills. Thus, the use of bottle cap media proved to be effective in enhancing the fine motor abilities of early childhood learners. This study implies that teachers can utilize simple, inexpensive, yet creative media such as bottle caps to create engaging, meaningful, and enjoyable learning experiences that support children’s holistic growth and development.